Computational hemodynamics of aortic aneurysms and dissections: flow patterns, blood rheology, wall mechanics, and clinical implications - Bayrakçı, Hakan; Çutay, Arif; Çermik, Özdeş (Fırat Evirgen, 2026)
Abdominal and thoracic aortic aneurysms (AAA and TAA) are complex vascular pathologies for which rupture and dissection risk assessment based solely on maximum diameter has proven insufficient. Accumulating clinical and computational evidence indicates that aneurysm progression is governed by coupled interactions between vascular geometry, blood rheology, flow patterns, wall mechanics, and intraluminal thrombus formation. This review provides a structured and critical synthesis of computational hemodynamics studies on aortic aneurysms and dissections, with emphasis on methodological choices that influence hemodynamic predictions and their mechanistic interpretation. Patient-specific computational fluid dynamics (CFD) and fluid--structure interaction (FSI) studies are reviewed with respect to flow patterns, wall shear stress (WSS), and derived biomarkers, including time-averaged WSS, oscillatory shear index, and residence-time–based metrics. Disturbed flow regimes characterized by recirculation, vortex formation, and oscillatory shear are consistently associated with intraluminal thrombus deposition, wall degeneration, and increased susceptibility to rupture, even in aneurysms below conventional surgical thresholds. The review further highlights the influence of non-Newtonian blood rheology and hematocrit-dependent viscosity variations on shear-related metrics, examines the role of wall compliance through FSI modeling, and discusses advances in imaging-based validation. Overall, the findings support a shift from diameter-centric criteria toward mechanistically informed, function-based risk stratification for personalized assessment of aortic aneurysm progression and rupture risk.
Keywords: Bioinformatic Methods Development; Biyoinformatik Yöntem Geliştirme; Biological Mathematics; Biyolojik Matematik